Antioxidant and immunomodulatory activities of Oviductus ranae in mice (Brazilian Journal of Pharmaceutical Sciences, 2018)
Oviductus ranae (OR) is a traditional Chinese medicine, which was first recorded in the Compendium of Materia Medica in the Ming Dynasty. OR contains high amounts of proteins and elicits therapeutic effects on neurasthenia, insomnia, and respiratory symptoms, which are related to oxidative stress and immunodeficiency. This study aimed to obtain the potential of OR for the development of functional food possessing antioxidant and immune-enhancement functions in the same dose. In antioxidant evaluation, OR can significantly decrease malondialdehyde and protein carbonyls (P < 0.05, P < 0.01) and significantly increase total superoxide dismutase and glutathione in a dose-dependent manner (P < 0.05, P < 0.01) against ethanol-induced oxidative stress in mice at 0.1, 1.0, and 3.0 g/kg BW. In immunomodulatory evaluation, OR could significantly enhance the phagocytosis of liver macrophages (P < 0.05, P < 0.01), delayed-type hypersensitivity response (P < 0.05, P < 0.01), hemolytic activity (P < 0.05), antibody-producing cells (P < 0.05), and natural killer cell activity (P < 0.05) in the same dose range described in antioxidant evaluation compared with those in the normal control. OR slightly influenced lymphocyte proliferation, peritoneal macrophage phagocytosis, and immune organ indices in mice. Thus, 3.0 g/kg BW OR showed potential for the development of functional food with antioxidant and immune-enhancement activities.